Synthesizing the best approach for the management of cancer related fatigue in children - Kholisa, Itsna Luthfi (International Journal of Research in Medical Sciences, 2017)
Fatigue has been recognised as a symptom that affects 39%-90% of patients undergoing anti-cancer therapyy. Fatigue is considered as the most frequently reported physical problem in children with cancer yet the most distressing symptoms of cancer therapy for children undergoing anti-cancer treatment. The effective diagnosis and treatment of fatigue will improve patient’s quality of life. A thorough review of current literature is needed to understand the best approach for managing this problem. A review of several literature regarding cancer-related fatigue management from the last decade was conducted in 2012. As many as eight studies were identified as the qualified paper to summarise the best approach towards fatigue in pediatric cancer patient. Excercise, massage therapy, drug therapy and psychosocial therapy were synthesised as four different approaches that effectively applyed to manage fatigue in children patients as a single modality. Fatigue-nursing intervention and the National Comprehensive Cancer Network (NCCN) Fatigue Practice Guidelines were multi-modality approaches that offer better option for the mangement of cancer-related fatigue in pediatric patients. The NCCN Fatigue Practice Guidelines seem to be the most effective approach for cancer-related fatigue management.